The Agrarian Buildings in Suburban Areas as a Territorial Heritage - García-Martín, Miguel; Villar-Lama, Arsenio (Revista de Estudios Andaluces, 2018)
This article aims to approach the current state of the haciendas in the Sevillian Aljarafe, considered today as patrimonial assets and as representative elements of the traditional rural landscape. From a previous inventory of 1981 and field work, it has been generated a database that integrates the basic information of each building: current permanence, environment, use, state of conservation, scientific and institutional recognition, and social valuation. After analyzing the results of this geographic inventory, we conclude that the haciendas have experienced a limited institutional attention despite its remarkable and emerging social value (for example as a place of events). This fact allows establishing links with other peri-urban areas with an important agrarian legacy.